195k views
1 vote
If f(x)= x^2-2x and g(x)=6x+4, for which value of x does (f+g)(x)=0

2 Answers

1 vote

Answer:

all work is shown and pictured

If f(x)= x^2-2x and g(x)=6x+4, for which value of x does (f+g)(x)=0-example-1
User Dishant Walia
by
5.1k points
0 votes

Answer:

x = - 2

Explanation:

The problem might be easier if you wrote what (f + g)(x) means.

f(x) + g(x) = 0 is what the equations means from which you get.

x^2 - 2x + 6x + 4 = 0

x^2 + 4x + 4 = 0 This factors into

(x + 2)^2 = 0

Take the square root of both sides.

sqrt(x+2)^2 = sqrt(0)

x + 2 = 0

x = - 2

User TreyBake
by
6.0k points